2005
DOI: 10.1089/tmj.2005.11.124
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Telemedicine for Delivering Continuing Medical Education in Rural Communities

Abstract: Physicians in rural communities have limited access to continuing medical education (CME) opportunities. We hypothesized that CME could be delivered via a telemedicine network as effectively as in-person. Our institution delivers CME lectures and grand rounds in Burlington, Vermont, for in-person attendees, and also via a telemedicine network that links 14 hospitals in Vermont and rural northeastern New York. All participants complete an evaluation questionnaire to receive CME credit. We compared the questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…15 Ricci et al have reported effectiveness of tele-education in training the health-care professional staying at distant sites. 16 Comparable results were obtained by Bertsch et al in education of medical students. 17 Limitations of training material and instructors can affect the transfer of knowledge and skill to trainees.…”
Section: Discussionmentioning
confidence: 68%
“…15 Ricci et al have reported effectiveness of tele-education in training the health-care professional staying at distant sites. 16 Comparable results were obtained by Bertsch et al in education of medical students. 17 Limitations of training material and instructors can affect the transfer of knowledge and skill to trainees.…”
Section: Discussionmentioning
confidence: 68%
“…Videoconferencing systems have experienced significant growth in recent years because of increased digital transmission options at reduced costs, vast improvements in video compression technologies, and improvements in the systems with an associated decrease in their cost. Several studies have Enhancing rural physician CME/CPD e503 demonstrated that CME/CPD videoconferencing is popular with rural physicians (Langille et al 1998;Davis & McCracken 2002;Klein et al 2005;Ricci et al 2005;Greenwood & Williams 2008), and is as effective, if not better, than faceto-face CME/CPD in increasing knowledge in a variety of clinical topic areas (Hampton et al 1994;Ricci et al 2005;Rossaro et al 2007;Miller et al 2008).…”
Section: Strategies To Enhance Cme/cpd Access For Rural Physiciansmentioning
confidence: 99%
“…Telemedicine could expand the educational tools available in rural areas and potentially allow the teaching of medical skills remotely. 2,3 However, there is little published information in which tele-education has been compared to conventional lecturing. 4 -9 The purpose of the present study was to determine if particular knowledge and wound management skills, including suturing, stapling and liquid tissue adhesive use, could be learned by novice paramedics as effectively via tele-education as by conventional face-to-face teaching.…”
Section: Introductionmentioning
confidence: 99%